Urban-rural linkages for nutrition: Territorial approaches for sustainable development - Garrett, James; Grigoletto, Riccardo; Egal, Florence; Forster, Thomas; Oenema, Stineke (United Nations Systems Standing Committee on Nutrition, 2020)
This paper provides, first, an overview of nutrition and the urban–rural context and how, in general terms, this relates to integrated territorial governance and development. The discussion is then situated in the context of the global development agenda, particularly initiatives dealing with nutrition, urban settlements and urban–rural linkages. The paper then explores how the Guiding Principles for Urban–Rural Linkages (URL-GP) and Framework for Action (FfA) developed by UN-Habitat relate to nutrition actions. Recognizing that the links between urban-rural linkages are not direct, but mediated by other systems and factors, and noting that experiences with applying a territorial approach to nutrition policies and programs are still limited, the paper concludes by outlining initial steps towards promoting more integrated territorial planning for nutrition, while also encouraging further thinking, initiatives and research in this direction.